Analiza wykorzystania ubezpieczenia w zarządzaniu ryzykiem przez przedsiębiorstwa z terenu Dolnego Śląska - Kwiecień, Ilona; Borda, Marta (Analysis of using insurance in risk management by enterprises from the Lower Silesia region, 2006)
Due to economic transformation in Poland the commercial insurance is becoming an important business risk management method. Growing competition, joining into UE insurance single market and many other macroeconomic factors should have an important significance for the range of demand on insurance. The paper presents the analysis of using the commercial insurance by enterprises. The analysis is based on questionnaire surveys conducted by the authors on the sample of firms from the Lower Silesia region. The results have been compared with similar surveys conducted countrywide by Polish Central Statistical Office taking into account trends of development in the last 5 years. Considering the size of the article the analysis is limited to voluntary non-life insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 266-273